Computed tomography of blunt renal trauma - Md Ralib @ Md Raghib, Ahmad Razali; Abdul Aziz, Azian (Singapore Medical Association, 2010)
Renal injury is observed in 10 percent of cases of abdominal trauma, and the majority (80 percent to 90 percent) of these are attributable to blunt trauma. Intravenous urography and ultrasonography of the abdomen were previously the modalities of choice in the imaging of renal injuries. However, computed tomography (CT) is currently the imaging modality of choice in the evaluation of blunt renal injury, since it provides the exact staging of renal injuries. The purpose of this article is to describe the CT staging of renal injuries observed in blunt abdominal trauma based on the Federle Classification and the American Association for the Surgery of Trauma renal injury severity scale.